A comparison between the effects of medial septal lesions and entorhinal cortex lesions on performance of nonspatial working memory tasks and reversal learning. - Yee, B; Rawlins, J (1998)
Rats with either electrolytic medial septal lesions or cytotoxic entorhinal lesions were compared to unoperated controls on a series of delayed matching-to-sample (DMS) tasks. A DMS trial consisted of two runs. In the first (information) run, the subject was familiarized with a sample discriminandum. In the second (choice) run, the subject was required to discriminate the sample discriminandum from a novel one. When a set of 20 discrete complex objects were used as discriminanda and each discriminandum was used once per day, neither lesions impaired choice accuracy. However, when a single pair of simple discriminanda was employed and re-used between trials within a day, rats with medial septal lesions were severely impaired whereas rats with entorhinal lesions performed at a level comparable to unoperated controls. Next, proactive interference was demonstrated by the introduction of an extra run prior to the information run. When this extra (pre-information) run required the subjects to visit the (eventual) negative discriminandum such that correct choice had to be guided by relative familiarity judgement, choice performance was reduced. Neither lesion group was selectively affected by this manipulation. But when the relative reinforcement history of the pre-information run and the information run was manipulated, such that a correct response required the subject to approach a discriminandum that had recently been non-rewarded, rats with entorhinal lesions were selectively impaired. The effect of delay was demonstrated when a 20-s interval was imposed between information run and choice run. This reduced overall choice accuracy, and this effect appeared to be more pronounced in both lesion groups, although not significantly so. Finally, neither lesion affected the acquisition of a simple discrimination task, but reversal learning was selectively enhanced in the entorhinal lesion group.